Heritage and Stigma. Co-producing and communicating the histories of mental health and learning disability. Issue 2 (30th May 2017) - Ellis, Rob
Abstract : University engagement with mental health services has traditionally been informed by the vocational and pedagogical links between the two sectors. However, a growth in the interest in public history and in the history of mental healthcare has offered new opportunities for those in the humanities to engage new audiences and to challenge perceptions about care in the past. The introduction of the 'impact agenda' and related funding streams has further encouraged academics to contribute to historical debates, and to those concerning current services. One such example of this is the Arts and Humanities Research Council funded Heritage and Stigma project at the University of Huddersfield, which was conceived to support mental health and learning disability charities in the exploration and dissemination of their own histories. Using this project as a case study, this paper will draw on primary source material to reflect on the opportunities and challenges of working in partnership with such groups. In particular, it will consider the need to address issues of stigma and exclusion in tandem with a critical understanding of the moves to 'community care' instigated by landmark legislation in the form of the 1959 Mental Health Act. Overall, it provides evidence of an inclusive, coproductive model of design and highlights the positive contribution to communicating mental health made by those based in the humanities.